Factors affecting fatal crash involvement of older drivers in the U.S. - Rallabandi, Abhiteja (Kansas State University, 2009)
Rapid increases are estimated in the percentage of elderly among the U.S. population starting in 2010. A majority of the older Americans depend on automobiles to meet their transportation needs either because of lack of public transportation or by choice. Ninety percent of total trips made by the elderly are by personal vehicle and seventy percent of this number involves the elderly driving the vehicles. However due to the aging process, older drivers experience a natural decline in sensory, cognitive, and other mental and physical capabilities as compared to younger drivers. This situation, combined with an imperfect highway infrastructure is making older drivers one of the most critical groups in terms of highway safety, thus demanding safer driving conditions. Safety concern for older drivers arises when the fatality rate per mile driven is considered, as exposure is one of the crucial factors contributing to increased fatality risk of older drivers. Hence, exposure reported in Billion Vehicle Miles Traveled (BVMT) was considered for this study. Crash data and exposure data were used to compute the fatality rates. Sources for this data are the Fatality Analysis Reporting System (FARS) and National Household Travel Survey (NHTS). A basic characteristics study was completed to compare the fatality risk of younger (16-24 yrs), middle-aged (25-64 yrs), and older drivers (65+ yrs). Crash details were screened to study the characteristics of older drivers involved in fatal crashes. Risk for older drivers due to other involved drivers of all ages divided into groups was studied to understand their distribution. A number of statistical methods like the chi-square test of independence, odds ratio and double paired comparison estimates were applied to study contributing factors of older driver’s increased fatal crash involvement. Results from the characteristics study for the elderly indicate that a majority of fatal crashes occur under daylight conditions with relatively higher seatbelt usage and non-alcoholic driving on straight level roads, which are generally considered as safer driving conditions. Other factors studied include vehicle-related variables like body type; manner of collision; roadway-related variables like roadway function class, month of the crash, and day of the week; and driver-related variables like race. Roadway functional class, vehicle body type, travel speed, number of drunk drivers, and the month in which the fatality occurred were found to have strong correlation with age of the older driver. Results from paired comparisons were used to estimate the fatality risk of older occupants as drivers and passengers under two different conditions considered simultaneously. Older drivers were found to have more fatality risk compared to older passengers. Recommended measures are also discussed to enhance older driver safety in the U.S.
Keywords: older drivers; fatal; FARS; exposure; crash; BVMT; Engineering, Civil (0543); Transportation (0709)